HUBUNGAN KELINCAHAN DENGAN KEMAMPUAN DRIBBLING SEPAKBOLA PADA TIM SMPN 1 LOGAS TANAH DARAT KECAMATAN LOGAS TANAH DARAT - Irawadi '; Ramadi '; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
ABSTRACT, The problem in this research is dribbling soccer ability player on Team SMPN 1 Logas Tanah Darat District of Logas Tanah Darat has not been so good. This is presumably because of the agility. So, the purpose of this study to determine the corelational agility with soccer dribbling ablity on Team SMPN 1 Logas Tanah Darat District of Logas Tanah Darat. This study is a correlational study by comparing the measurement results of two different variables, in this study a sample of the entire football player Team SMPN 1 Logas Tanah Darat with a total of 18 people. Based on analysed of data that large correlation value agility with dribling soccer ability team SMPN 1 Logas Tanah Darat District of Logas Tanah Darat is r count of 0597 In the table of values (Product Moment) (5%) of = 0468, or 0597> 0468 this means r count> r table, means Ho rejected means that the hypothesis is accepted linear regression model. Further testing the hypothesis by using the formula t test Significance. From the calculation results are known t = 2974 while ttabel with dk = n-2 = 18-2 = 16 at 95% confidence level is 1.746. Criteria for hypothesis testing Ho accepted if thitung smaller than ttabel, but the result of the calculation shows that (thitung> ttabel) or 2,974> 1,746., And is therefore null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) that "there is corelation agility with dribling soccer ability on team football at SMPN 1 Logas Tanah Darat District of Logas Tanah Darat. "accepted.Keywords : Agility, Dribbling, Soccer